Parametrización, simulación CFD y construcción de rodetes para analizar la influencia del número de álabes en el funcionamiento de la bomba hidráulica. - Cueva Torres, Edgar Ricardo (2021)
The present investigation shows a study about how fluid flows inside a centrifugal pump, this was made by modifying and getting done different geometric configurations of impellers (number of vanes); analyzing in this, the interaction between impellers and the pump casing using a mathematical model elaborated from fluid mechanics equations seen before. After this, was developed a computational fluid dynamics (CFD) based on a 3D model of the casing, impeller, and other different parts of the pump. Finally, all the data obtained before is validated by the construction and installation of an experimental hydraulic system, allowing putting on and off the different impellers easily, obtaining in three processes, the operating parameters such as flow rate and manometric head (total head developed by the pump). The objective of the study was, analyze, and compare the influence of the number of vanes on semi-opened radial impellers in the theoric and real operating of a centrifugal pump. The results show that the influence of the number of vanes for this case of design and analysis is notorious in the first four impellers, reaching acceptable results for flow rate and head. From that, the influence of data measured with the five vanes impeller decreases by 5% from the available flow rate, and in a fewer range, the head the impeller gets, is 0.86%. Key words: Ecuaciones de Euler, bombas radiales, impulsores semi-abiertos, simulación CFD, mecanizado de impulsores.